2017
DOI: 10.21767/1791-809x.1000492
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Barriers Related to the Use of Latrine and Health Impacts in Rural Kebeles of Dirashe District Southern Ethiopia: Implications for Community Lead Total Sanitations

Abstract: Unsanitary disposal of human excreta, together with unsafe drinking water and poor hygiene conditions contribute for 88% of diarrheal diseases; the burden of this disease is a leading cause of morbidity and mortality particularly in young children and lack of access to sanitation has significant non-health consequences, especially for women and girls, including lack of security and privacy, decreased school attendance and basic human dignity. In addition, inadequate sanitation is implicated in Helminth infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
1
10
2
Order By: Relevance
“…Though many knew the benefit of latrine utilization, significant number of them use latrine because it is convenient particularly for females as compared with open defecation. This finding is similar with the result of South Ethiopia, but higher than Northwest Ethiopia [20,24]. This might be because of lack of awareness.…”
Section: Discussionsupporting
confidence: 90%
“…Though many knew the benefit of latrine utilization, significant number of them use latrine because it is convenient particularly for females as compared with open defecation. This finding is similar with the result of South Ethiopia, but higher than Northwest Ethiopia [20,24]. This might be because of lack of awareness.…”
Section: Discussionsupporting
confidence: 90%
“…The dependent variable was OD practice. 10,13,14,[27][28][29][30][31][32] Qualitative data collection took place in February 2018. Using an FGD protocol, 3 FGDs were done in Nakwamekwi, 2 in Napetet, 3 in Kanamkemer, and 2 in Kawalathe.…”
Section: Research Instrumentsmentioning
confidence: 99%
“…Other research also states that the low use of latrines is shown by the existence of people who defecate openly outside the home, the low altitude of the community towards the use of latrines. As the reason why they do that is because of the low knowledge of negative impacts on health, and working conditions that are outside the home [9].…”
Section: Discussionmentioning
confidence: 99%